Structure elucidation of a bioactive fucomannogalactan from the edible mushroom Hypsizygus marmoreus - Oliveira, Ruberney S.; Biscaia, Stellee M. P.; Bellan, Daniel L.; Viana, Sthefany R. F. [UNESP]; Di-Medeiros Leal, Maria Carolina; Vasconcelos, Ana Flora D. [UNESP]; Liao, Luciano M.; Trindade, Edvaldo S.; Carbonero, Elaine R. (Elsevier B.V., 2019)
A fucomannogalactan (FMG-Hm), with a molecular weight of 17.1 kDa, obtained from fruiting bodies of Hypsizygus marmoreus exhibited promising in vitro antimelanoma effects. FMG-Hm was not cytotoxic, nor did it alter the cell morphology and proliferation, but was able to inhibit colony-forming ability and cell migration in B16-F10 murine melanoma cells. An analysis of the monosaccharide composition indicated that FMG-Hm was composed of fucose, mannose, and galactose in a ratio of 1.00:1.08:3.17. The FMG-Hm was structurally characterized based on methylation analysis, partial acid hydrolysis, and NMR experiments. The results indicated that FMG-Hm contained a alpha-(1 -> 6)-linked galactopyranosyl main chain, partially substituted at O-2 by non-reducing ends of alpha-L-fucopyranose and beta-D-mannopyranose. The predicted structure of the heteropolysaccharide was established as: [GRAPHICS] .
Keywords: Hypsizygus marmoreus; Mushroom; Fucomannogalactan; Chemical structure; Antimelanoma; B16-F10 cell